DOES FOREIGN AID REDUCE ENERGY AND CARBON INTENSITIES OF DEVELOPING ECONOMIES?. (1st June 2011) - Kretschmer, Bettina; Hübler, Michael; Nunnenkamp, Peter
Abstract Advanced OECD countries are widely held responsible for containing global carbon emissions by providing financial and technical support to developing economies where emissions are increasing most rapidly. It is open to question, however, whether more generous official development assistance would help fight climate change effectively. Empirical evidence on the effects of foreign aid on energy and carbon emission intensities in recipient countries hardly exists. We contribute to closing this gap by considering energy use and carbon emissions as dependent climate‐related variables and the volume and structure of aid as possible determinants. In particular, we assessed the impact of aid that donors classify to be specifically related to energy issues. We performed dynamic panel Generalised Method of Moments and Least Squares Dummy Variable Corrected estimations. We found that aid tends to be effective in reducing the energy intensity of GDP in recipient countries. All the same, the carbon intensity of energy use is hardly affected. Scaling up aid efforts would thus be insufficient to fight climate change beyond improving energy efficiency. Copyright © 2011 John Wiley & Sons, Ltd.